Sublingual and subcutaneous allergen-specific immunotherapy as a method of treatment of patients with inhalant allergy – a review of the literature - Pawlak, Angelika; Ręka, Gabriela; Korzeniowska, Anna; Piecewicz-Szczęsna, Halina (Medical Studies/Studia Medyczne, 2021)
Allergy is the result of the body’s intolerance to harmless antigens. In the treatment of respiratory allergies, allergen immunotherapy (AIT) is a causal method of treating allergies. It can be carried out via the subcutaneous route (SCIT) or the sublingual route (SLIT) – in the form of drops or tablets. Desensitisation is recommended from the age of 5 years, and the doses of the drug should be repeated gradually so that the body acquires immunological tolerance to allergens. Thirty-six current publications from the PubMed and Google Scholar platforms were reviewed. A series of studies confirming the safety, efficacy, and good tolerability of both types of AIT in children and adults were referred to. The results presented in the review show the similarities and differences between the desensitisation methods. They differ, among other things, in the convenience of use, the price, the frequency of side effects of treatment, and the dosage.